Unveiling Corruption: A Game With The Purpose of Give Thought to Environmental Corruption Topics - Abreu, Vinicius Santos De; Classe, Tadeu Moreira de; Castro, Ronney Moreira de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Corruption is a worrying topic worldwide because it is the primary source of issues related to social problems, environmental crimes, ineffective health, low education, and other contexts. Problem: In this scenario, citizens, the most harmed actors in corruption scenarios, can become the main weapon against it. By providing information and giving them chances to get knowledge and think critically, they could fight against corrupt situations. Nevertheless, it is a non-trivial task. Solution: Thus, we present the game Green Greed in this paper. Considering the teaching and learning features already recognized in games with a purpose, our game gives information that allows citizens to think critically about environmental corruption and its relation to climate change. IS Theory: We based the game design process on the rhetorical theory because, using it, we could present critical information and persuade our audience by the crucial problem that the game approaches. Method: We evaluate the game using a quasi-experiment to analyze the player’s perception of the game’s pedagogical subject, rhetorics, and critical thinking. We analyzed data by quantitative methods such as descriptive and inferential statistics. Summary Results: We observed evidence that players perceived the game elements related to pedagogical subjects, rhetorics, and critical thinking. Also, we could observe the correlation among these game elements. Contributions to IS: Thus, this study brings contributions to the SI area by proposing games as supporting tools to make citizens learn and think about corruption issues. In addition, beyond the social relevance of this theme, the research is aligned with the GranDSI-BR 2016-2026 and GranDGamesBR 2020-2030.